2008
DOI: 10.1007/s10561-008-9112-1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of radiation-sterilised human Bone-Tendon-Bone grafts preserved by different methods

Abstract: Patellar tendon auto- and allo-grafts are commonly used in orthopedic surgery for reconstruction of the anterior cruciate ligaments (ACL). Autografts are mainly used for primary reconstruction, while allografts are useful for revision surgery. To avoid the risk of infectious disease transmission allografts should be radiation-sterilised. As radiation-sterilisation supposedly decreases the mechanical strength of tendon it is important to establish methods of allograft preservation and sterilisation assuring the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 9 publications
1
24
1
Order By: Relevance
“…A possible reason for this Wnding lies in the use of high-dose gamma irradiation for sterilization [41]. Kaminski et al [23] carried out mechanical tests at baseline and concluded that adequate results can be achieved using deep-frozen transplants with additional irradiation. They did not take into account the ligamentization process.…”
Section: Discussionmentioning
confidence: 99%
“…A possible reason for this Wnding lies in the use of high-dose gamma irradiation for sterilization [41]. Kaminski et al [23] carried out mechanical tests at baseline and concluded that adequate results can be achieved using deep-frozen transplants with additional irradiation. They did not take into account the ligamentization process.…”
Section: Discussionmentioning
confidence: 99%
“…The local immune response, although visible, has no effect on the incorporation of the allogeneic graft. A commonly applied conservation method is irradiation of the fascia in a physiological salt solution with 33 kGy [21]. Based on nine randomized clinical studies featuring 208 subjects and 858 gingival recessions Graziani et al [22] discussed the effectiveness of periodontal plastic procedures in covering multiple gingival recession defects.…”
Section: Discussionmentioning
confidence: 99%
“…Electron beam is a high energy electron treatment which is currently used for sterilization of medical devices and in radiation therapy. A number of tissue banks have used accelerated electron beam for sterilization of human tissues [25,41,42] . As compared to gamma radiation, accelerated electron beam has lower penetration into the material.…”
Section: Methods For Sterilization Of Tissue Allograftsmentioning
confidence: 99%